1985
DOI: 10.1111/j.1600-9657.1985.tb00561.x
|View full text |Cite
|
Sign up to set email alerts
|

External root resorption following bleaching of pulpless teeth with oxygen peroxide

Abstract: Cvek M, Lindvall A-M. External root resorption following bleaching of pulpless teeth with oxygen peroxide. Endod Dent Traumatol 1985; 1: 56-60.Abstract -Eleven teeth in which bleaching with 30% oxygen peroxide was followed by external root resorption are presented. One tooth had no traumatic history, while the others were previously subluxated or luxated in accidental injury. Radiographic appearance of resorptions varied. In 2 teeth the resorptions were only superficial and did not progress during the observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
11

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 10 publications
2
71
0
11
Order By: Relevance
“…A high concentration of hydrogen peroxide in combination with heating seemed to promote cervical root resorption (Friedman et al, 1988;Baratieri et al, 1995), in line with observations made in animal experiments (Madison and Walton, 1990;Rotstein et al, 1991b;Heller et al, 1992). The underlying mechanism for this effect is unclear, but it has been suggested that the bleaching agent reaches the periodontal tissue through the dentinal tubules and initiates an inflammatory reaction (Cvek and Lindvall, 1985). It has also been speculated that the peroxide, by diffusing through the dentinal tubules, denatures the dentin, which then becomes an immunologically different tissue and is attacked as a foreign body (Lado et al, 1983).…”
Section: (Iv-4) Adverse Effectsmentioning
confidence: 64%
“…A high concentration of hydrogen peroxide in combination with heating seemed to promote cervical root resorption (Friedman et al, 1988;Baratieri et al, 1995), in line with observations made in animal experiments (Madison and Walton, 1990;Rotstein et al, 1991b;Heller et al, 1992). The underlying mechanism for this effect is unclear, but it has been suggested that the bleaching agent reaches the periodontal tissue through the dentinal tubules and initiates an inflammatory reaction (Cvek and Lindvall, 1985). It has also been speculated that the peroxide, by diffusing through the dentinal tubules, denatures the dentin, which then becomes an immunologically different tissue and is attacked as a foreign body (Lado et al, 1983).…”
Section: (Iv-4) Adverse Effectsmentioning
confidence: 64%
“…37 In vitro studies using extracted teeth showed that hydrogen peroxide placed in the pulp chamber penetrated the dentine, 38 that heat increased the penetration 39 and that the penetration is greater in teeth with cervical cemental defects. 40 Intracoronal bleaching with 30% hydrogen peroxide reduces the microhardness of dentine and enamel 41 and mechanically weakens the dentine.…”
Section: Opinionmentioning
confidence: 99%
“…26,27 Bu yüz-den önceden yapılan kontrollerle erken teşhis konulabilmektedir. Yaptığımız olgularda hastalar 3 ve 6 ay sonra kontrole çağırılmışdır.…”
Section: Discussionunclassified